PENGARUH SiLPA DAN KETERGANTUNGAN FISKAL TERHADAP BELANJA MODAL KABUPATEN/KOTA DI PULAU SUMATERA DENGAN KLASIFIKASI PEMERINTAH DAERAH SEBAGAI PEMBEDA - Zeatifani, Desi; Abdullah, Syukriy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The objective of the research was to find out the influence of SiLPA and Fiscal Dependency on Capital Expenditure simultaneously and partially in Province/City Government of Sumatera Island with classification of local government as a differentiator. The research used causal design. The population was 136 provinces/cities in Aceh, and whole observed. The period of observation was since 2013 until 2015, so there were 408 analysis units all together. The data were processed by using multiple linear regression tests with an SPSS software program. The result of the research showed that SiLPA and Fiscal Dependency both simultaneosly and partially influenced Capital Expenditure if no differentiator variable. SiLPA and Fiscal Dependency on classification of capital expenditures by local governments as differentiator variables showed different effects in each classification that classification A, B and C.